Cover Picture: Selective Reductions of N, N‐Bischloro(aryl)‐phosphino‐amines Yielding Three‐, Five‐, Six‐, and Eight‐Membered Cyclic Azaphosphanes (Chem. Eur. J. 18/2017). Issue 18 (14th February 2017) - Höhne, Martha; Joksch, Markus; Konieczny, Katharina; Müller, Bernd H.; Spannenberg, Anke; Peulecke, Normen; Rosenthal, Uwe
Abstract : The finding of the cyclic structure of PNP‐containing compounds is compared to the discovery of the cyclic structure of benzene in 1865 by Kekulé. He told of dreaming of dancing atoms, moving snake‐like resulting in an ouroboros—the serpent eating its own tail. This brought him to the idea of the cyclic structure of benzene. In 1886 the German Chemical Society humorously adopted his idea and published a cyclic structure consisting of six monkeys holding hands. The formation of cyclic compounds is the quintessence of this publication and is illustrated in this abstract way. More information can be found in the Full Paper by U. Rosenthal et al. onpage 4298 ff.